Stress intensity and coping strategies associated with the mental health of professional and college level baseball players - Huang, C. C. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: The purpose of this study was to clarify the stress intensity and reaction, coping strategies and social support of professional and college group-A baseball athletes. Since stress can cause physiological and psychological reactions and hence affect the body, the correlation between stress and psychiatric morbidity will also be examined. Moreover, the coping strategies and the level social support were used to predict the intensity and reactions to stress. Methods The Stress Intensity and Reaction Questionnaire, Chinese Health Questionnaire, Coping Strategies Inventory and Social Support Questionnaire were used as the survey tools in this study. 124 professional baseball athletes and 130 college group-A baseball athletes were recruited as subjects. The data were analysed to provide mean vales, standardized scores, ANOVA, t-tests, Pearson productmoment of correlation and stepwise regression. Results There wasNo significant difference was found for stress status between professional baseball athletes and college group-A baseball athletes. The probability of psychiatric morbidity in college group-A baseball athletes is significantly higher than that of professional baseball athletes. There was positive significant correlation between reactions of stress and psychiatric morbidity in all baseball athletes, with a higher score of psychiatric morbidity suugesting that greater reactions to stress may occur. Additionally, professional baseball athletes were found to use more engagement coping strategies than college group-A baseball athletes, such as problem-focused strategies. Finally, no significant differences were found for the variables of social support. Conclusions Coping strategies and psychiatric morbidity can predict the reactions to stress in professional and college level baseball players. The findings of this study offers suggestions for coaches and the baseball athletes with regard to management of psychological stress.